2010
DOI: 10.1074/jbc.m110.149468
|View full text |Cite
|
Sign up to set email alerts
|

Statins Promote the Degradation of Extracellular Amyloid β-Peptide by Microglia via Stimulation of Exosome-associated Insulin-degrading Enzyme (IDE) Secretion

Abstract: Epidemiological studies indicate that intake of statins decrease the risk of developing Alzheimer disease. Cellular and in vivo studies suggested that statins might decrease the generation of the amyloid ␤-peptide (A␤) from the ␤-amyloid precursor protein. Here, we show that statins potently stimulate the degradation of extracellular A␤ by microglia. The statin-dependent clearance of extracellular A␤ is mainly exerted by insulindegrading enzyme (IDE) that is secreted in a nonconventional pathway in association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
174
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(183 citation statements)
references
References 67 publications
(73 reference statements)
9
174
0
Order By: Relevance
“…Indeed, previous evidence showed that neuron-derived EMVs contain some components of the gsecretase complex, 57 whereas the insulin-degrading enzyme, which proteolyzes Ab 1-42 and Ab 1-40, has been detected among cargo proteins of microglial EMVs. 58 The significant decrease in neurotoxicity observed upon pretreatment with anti-Ab antibodies strongly supports the theory that neurotoxic Ab forms are in fact localized to the outer lipid bilayer of MVs. However, further studies are required to unequivocally define the topology of Ab species and to clarify whether Ab forms are actually associated to the extracellular membrane of shed MVs.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, previous evidence showed that neuron-derived EMVs contain some components of the gsecretase complex, 57 whereas the insulin-degrading enzyme, which proteolyzes Ab 1-42 and Ab 1-40, has been detected among cargo proteins of microglial EMVs. 58 The significant decrease in neurotoxicity observed upon pretreatment with anti-Ab antibodies strongly supports the theory that neurotoxic Ab forms are in fact localized to the outer lipid bilayer of MVs. However, further studies are required to unequivocally define the topology of Ab species and to clarify whether Ab forms are actually associated to the extracellular membrane of shed MVs.…”
Section: Discussionsupporting
confidence: 57%
“…Although it is indirect evidence, previous studies have shown that statin treatment increases IDE secretion, and inhibits protein prenylation. 35,41 Whether IDE secretion by statin treatment occurs through same pathway as Ab treatment should be investigated. Further, how IDE inside the lysosome is transported to the extracellular medium needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to our work, it was known that, as IDE has no signal sequences, it is secreted from the microglia via an exosome-associated unconventional secretory pathway under statin treatment. 35 To determine whether Ab-induced IDE secretion is associated with exosomes in astrocytes, both exosomes and nonexosome fractions were isolated from vehicle-or Ab-treated ACM. Ab increased the IDE secretion both in the exosomes and nonexosome fractions ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The half-life time of A␤ is ϳ8 -12 h in human cerebrospinal fluid and 3-4 h in the interstitial fluid of mouse brain, indicating efficient clearance mechanisms that counteract the production of A␤ (9, 10, 38). The clearance of A␤ from the brain involves internalization via pinocytosis or receptor-mediated endocytosis/phagocytosis (13-15, 39) and subsequent degradation in the endosomal/lysosomal compartments (40), transcytosis and drainage via the blood-brain barrier to the vasculature (12, 41), and proteolytic degradation of extracellular A␤ by cell surface-localized and secreted proteases (21,28,36).Microglial cells could contribute to the clearance of A␤, as they are the main phagocytes in the brain and also express several proteases at the cell surface that could degrade extracellular and internalized A␤ (27). Recent evidence demonstrated that microglia secrete substantial amounts of IDE, thereby allowing efficient degradation of monomeric A␤ variants also at some distance from the microglial cell (19,42).…”
mentioning
confidence: 99%